Genome Wide Mapping of NR4A Binding Reveals Cooperativity with ETS Factors to Promote Epigenetic Activation of Distal Enhancers in Acute Myeloid Leukemia Cells. - Ryan P Duren; Seth P Boudreaux; Orla M Conneely (PLoS ONE)
Members of the NR4A subfamily of orphan nuclear receptors regulate cell fate decisions via both genomic and non-genomic mechanisms in a cell and tissue selective manner. NR4As play a key role in maintenance of hematopoietic stem cell homeostasis and are critical tumor suppressors of acute myeloid leukemia (AML). Expression of NR4As is broadly silenced in leukemia initiating cell enriched populations from human patients relative to normal hematopoietic stem/progenitor cells. Rescue of NR4A expression in human AML cells inhibits proliferation and reprograms AML gene signatures via transcriptional mechanisms that remain to be elucidated. By intersecting an acutely regulated NR4A1 dependent transcriptional profile with genome wide NR4A binding distribution, we now identify an NR4A targetome of 685 genes that are directly regulated by NR4A1. We show that NR4As regulate gene transcription primarily through interaction with distal enhancers that are co-enriched for NR4A1 and ETS transcription factor motifs. Using a subset of NR4A activated genes, we demonstrate that the ETS factors ERG and FLI-1 are required for activation of NR4A bound enhancers and NR4A target gene induction. NR4A1 dependent recruitment of ERG and FLI-1 promotes binding of p300 histone acetyltransferase to epigenetically activate NR4A bound enhancers via acetylation at histone H3K27. These findings disclose novel epigenetic mechanisms by which NR4As and ETS factors cooperate to drive NR4A dependent gene transcription in human AML cells.